Innovative Management Approaches to Increasing the Financial Capacity of Banks - Vakhobov Shohjahon Valiyevich (Scientific Trends, 2024)
Increasing the financial potential of banks is one of the pressing problems of the economy. In this process, the introduction of innovative management methods is of great importance. This paper discusses the digitalization of banking activities, the development of financial technologies, and increasing financial potential through the use of modern management methods.
Keywords: Bank, financial potential, capital, business environment, business environment, minority shareholder, investor, investment, corporate governance, corporate structure, supply chain, cyber security.